A text mining analytics on online forum medical queries among parents with diabetic children - Kartiwi, Mira; Gunawan, Teddy Surya; Ab Rahman, Jamalludin (Wolters Kluwer Medknow Publications, 2020)
Introduction: Recent research shows how the advancement of Internet has changed how parents seek health information for their children in online forums and social media. This includes parents with children that suffer from chronic diseases, such as diabetes. However, little is known on the extent to which the Internet is being used to obtain health-related information and the common concerns raised. Objectives: To analyse the topical context of the public conversation and discussion on online forum among parents with diabetic children. Materials and Methods: Text mining technique was used to examine a dataset that contains granular user posts on online health parenting forum from July 2015 to March 2019. Results: The result of text mining shows that among the key information being sought were the details available non-medical treatments and social supports. Conclusion: The research implications of our results would help medical practitioners and policy maker to design appropriate supports for parents and community in preventing and managing diabetic as chronic disease.